A decision support system that incorporates price volatility in risk classifying regional food security. (19th April 2021) - Laryea, Rueben; Carling, Kenneth; Cialani, Catia
Consider a cooperative group of decision-makers striving to strategise against failing to attain a goal. The risk of failure depends on external factors and the decision-makers' assessment and acceptance of risk. This setting is complex due to multiple objectives and criteria, making it difficult for the individual and group of decision-maker(s) to assess the risk coherently. To aid humans in this situation formal risk frameworks such as utilities additives discriminants (UTADIS) have been developed. The contribution of this paper is to extend such framework with objective measures of volatility preserving its features. The solution is demonstrated and implemented on the problem of UN's policy-makers monitoring the sustainable development goal of food security. The solution provides both global risk scores and the utility threshold in an efficient manner such that misclassification between the decision-makers' preferred classification and their authentic classification is mimimised and obtained within one iteration.